204Section42009

# 204Section42009 - Econ 204 Section 4 GSI Hui Zheng Key...

This preview shows pages 1–2. Sign up to view the full content.

Econ 204 Section 4 GSI: Hui Zheng Key Words Metric Space, Normed Vector Space, Euclidean Space, Lipschitz-Equivalent, Convergence, Cluster Point, Increasing(Decreasing) Sequence, Lim Sups(Lim Infs), Rising Sun Lemma, Bolzano-Weierstrass Theorem Section 4.1 Metric Space metric space is a pair ( X;d ) , where X is a set and d : X ± X ! R + , satisfying 1. 8 x;y 2 X d ( x;y ) ² 0 ;d ( x;y ) = 0 , x = y 2. 8 x;y 2 X d ( x;y ) = d ( y;x ) 3. (triangle inequality) 8 x;y;z 2 X d ( x;y ) + d ( y;z ) ² d ( x;z ) Example 4.1.1 Let d ( x;y ) = max f x ³ y ; 1 g . Prove or disprove that ( R ;d ) is a metric space. Disproof: Let x 2 X . Then d ( x;x ) = max f x ³ x ; 1 g = max f 0 ; 1 g = 1 . So d is not a metric. Example 4.1.2 Let d ( x;y ) = min f x ³ y ; 1 g . Prove or disprove that ( R ;d ) is a metric space. Proof:: In fact this is called the standard bounded metric corresponding to d . Check the triangle inequality: d ( x;z ) ´ d ( x;y ) + d ( y;z ) Now if either x ³ y ² 1 or y ³ z ² 1 then the right side of this inequality is at least 1 ; 1 , the inequality holds. It remains to consider the case in which x ³ y < 1 and y ³ z < 1 . In this case, we have x ³ z ´ x ³ y + y ³ z = d ( x;y ) + d ( y;z ) : Hence d ( x;z ) = min f x ³ z ; 1 g ´ x ³ z ´ d ( x;y ) + d ( y;z ) : The triangle inequality holds. Example 4.1.3 Let X = [1 ; + 1 ) . Let d ( x;y ) = 1 x ³ 1 y . Prove or disprove that ( X;d ) is a metric space. Proof: 8 x;y 2 X; d ( x;y ) = 1 x ³ 1 y ² 0 and d ( x;y ) = 1 x ³ 1 y = 0 , x = y 8 x;y 2 X; d ( x;y ) = 1 x ³ 1 y = 1 y ³ 1 x = d ( y;x ) Check the triangle inequality. We show that d ( x;z ) ´ d ( x;y ) + d ( y;z ) will depend upon the ordering of x , y , and z . Because d ( x;z ) = d ( z;x ) , without loss of generality, we can assume x ´ z . Case 1. Suppose 1 x ² 1 y ² 1 z . Then d ( x;y ) + d ( y;z ) = 1 x ³ 1 y + 1 y ³ 1 z = 1 x ³ 1 y + 1 y ³ 1 z = 1 x ³ 1 z = 1 x ³ 1 z = d ( x;z ) Case 2. Suppose 1 x ² 1 z ² 1 y . Then d ( x;y ) + d ( y;z ) = 1 x ³ 1 y + 1 y ³ 1 z = 1 x ³ 1 y + 1 z ³ 1 y =

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 4

204Section42009 - Econ 204 Section 4 GSI Hui Zheng Key...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online